Using Subject Guides to Support Curriculum and Patient Care: A Multipronged Approach - Britton, Robert M.; Li, Jie (Medical reference services quarterly, 2019)
Even though the library subscribes to numerous valuable health science resources, many e-books are not being used by clinicians, researchers, and students. Because these resources are bundled in various packages that often do not show up in federated searches, making them more discoverable is important. At the same time, the cost of textbooks is increasingly burdensome for students. Using authoritative lists and metrics to evaluate these resources while also seeking faculty input to include the best resources in subject guides may not only benefit the faculty and students but also aid in promoting library resources.